AB1258 Characterization of the CDC anti-nuclear antibody (ANA) reference serum panel using multiplex and immunoprecipitation assays. (23rd January 2014) - Mahler, M.; Lakos, G.; Rönnelid, J.; Satoh, M.; Chan, E.K.; Fritzler, M.J.
Abstract : Background: Anti-nuclear antibodies (ANA) represent serological hallmarks of systemic rheumatic diseases (SARD), and have been traditionally identified by indirect immunofluorescence (IIF) on HEp-2 cells, followed by antigen-specific confirmation assays. Several new methodologies, such as ELISA, line immunoassays (LIA) and various multiplex assays have been recently developed. Objectives: This study evaluated the reactivity of the CDC ANA reference sera (Center for Disease Control, Atlanta, GA) using state of the art immunoassays and protocols. Methods: The ANA reference serum panel (CDC1-CDC12) was tested by two different addressable laser bead immunoassays (ALBIAs: QUANTA Plex SLE8, INOVA Diagnostics, USA and FIDIS Connective PROFILE Panel, BMD, France), three LIAs (EUROLINE ANA, Euroimmun, Germany; recomLine ANA/ENA IgG, Mikrogen, Germany and INNO-LIA, Innogenetics, Belgium), immunoprecipitation (IP) and by IIF on HEp-2 cells. IIF results were quantified using a digital imaging system (NOVA View: INOVA Diagnostics, Inc.). Novel reactivities of the CDC samples were based on obtaining consensus by at least two different methods. Results: In addition to the historically described reactivities, 6/12 sera demonstrated novel reactivities or fine specificities: CDC1 (IIF ANA, homogeneous/rim pattern; anti-double stranded DNA (dsDNA): SmBB', RNP-C; CDC2 (IIF ANA, speckled pattern; anti-SS-B/La): SS-A (Ro60), TRIM21/Ro52, SS-B (La); CDC3 (IIF ANA, speckled pattern): SS-A (Ro60), SS-B (La), RNP-68kDa; CDC4 (Anti-U1 RNP, nuclear RNP): RNP-68kDa, RNP-A; CDC5 (Anti-Sm): SmD, SmBB', RNP-68kDa, RNP-A, RNP-C; CDC7 (Anti-SS-A/Ro): SS-A (Ro60), TRIM21/Ro52; Jo-1. In addition, other specificities were identified with at least one method, including an IP band consistent with Su/Ago and Su 200k in CDC11 (Anti-PM/Scl), and a protein that may correspond to RNA helicase A in CDC12 (Anti-Ribosomal P). Using the NOVA View system, IIF pattern recognition of the five samples historically developed for ANA IIF testing where consistent with described patterns: CDC1 (homogeneous), CDC2 (speckled), CDC3 (speckled), CDC6 (speckled) and CDC8 (centromere). Nuclear intensities as determined by NOVA View and expressed as Light Intensity Units (LIU) were 1047 LIU (CDC1), 1461 LIU (CDC2), 1378 LIU (CDC3), 1822 LIU (CDC4), 1247 LIU (CDC5), 394 LIU (CDC6), 288 LIU (CDC7), 695 LIU (CDC8), 956 LIU (CDC9), 286 LIU (CDC10), 226 LIU (CDC11) and 39 LIU (CDC12). Conclusions: Based on our data we identified novel fine specificities of the CDC ANA reference sera. These new findings will be important in the ongoing standardization of autoantibody assays. Findings detected by only one method require confirmation. References: Chan EK, et al. AutoAbSC.Org – Autoantibody Standardization Committee in 2006. Autoimmun Rev 2007, 6:577-580. Disclosure of Interest: M. Mahler Employee of: INOVA Diagnositics Inc., G. Lakos Employee of: INOVA Diagnositics Inc., J. Rönnelid: None Declared, M. Satoh: None Declared, E. Chan: None Declared, M. Fritzler Consultant for: INOVA Diagnositics Inc.